2014
DOI: 10.14202/vetworld.2014.439-442
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on serum liver function indices of Diethylnitrosamine induced hepatocarcinogenesis and chemoprotective potential of Eclipta alba in male Wistar rats

Abstract: A preliminary study on serum liver function indices of Diethylnitrosamine induced hepatocarcinogenesis and chemoprotective potential of in male Wistar rats , 7( 6): 439-442. Eclipta albaVeterinary World

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…ROS play an important role in different types of cancer development [24]. Furthermore, NDEA increased oxidative stress through hepatic metabolism via the cytochrome p450 enzyme [25]. Ethyldiazonium ion alkylates nuclear DNA bases through NDEA to form adducts such as O4 and O6ethyldeoxythymidine and O6-ethyldeoxyguanosine [26].…”
Section: Discussionmentioning
confidence: 99%
“…ROS play an important role in different types of cancer development [24]. Furthermore, NDEA increased oxidative stress through hepatic metabolism via the cytochrome p450 enzyme [25]. Ethyldiazonium ion alkylates nuclear DNA bases through NDEA to form adducts such as O4 and O6ethyldeoxythymidine and O6-ethyldeoxyguanosine [26].…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of serum ALT, AST, and ALP activity indicates the abnormality of liver function [24]. And the increase of creatinine concentration in serum results in renal injury [25].…”
Section: Discussionmentioning
confidence: 99%
“…Various investigations have shown that toll-like receptors (TLRs) and their pro-inflammatory mediators may be of the host inflammatory response to infection and play a significant role in human hepatic disease. 23,36 Diethylnitramine (nitroso family compound), a wellknown hepato-carcinogenic agent, can be contained in water, tobacco smoke, agricultural chemicals, fried meals, cured meals, cheddar cheese, pharmaceutical and cosmetic products, and in trace amounts in baby bottle nipples. Studies suggest that the DEN-induced hepatocellular carcinoma in the rodents was similar to human hepatocellular carcinoma.…”
Section: Dovepressmentioning
confidence: 99%
“…34,41 Previous studies suggest that DEN was metabolized in hepatic tissue via the action of cytochrome p450 enzymes and finally increased oxidative stress. 23,36,42 During the metabolism in hepatic tissue and reactive with the various metabolites, these are mainly responsible for the hepatic toxic effects. DEN bioactivates the ethyldiazonium ion, which alkylates DNA bases to form promutagenic adducts like O6-ethyldeoxyguanosine and O4 and O6ethyldeoxythymidine.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation